Bathymetric ridges off Ras Spartel, western termination of the Strait of Gibraltar: Genetic considerations of singular shelf-margin morphological features - Pascal Le Roy; Francisco José Lobo; Ruth Durán; Debora Duarte; Léna Virat; Mohamed Sahabi; Marcaurelio Franzetti; Jacques Grall; Thierry Garlan (Geomorphology, 2026)

Sediment mobility over a dispersive inner shelf from combined wave and tide bed shear stress - Déborah Belleney; Nicolas Le Dantec; Pascal Le Roy; Alain Hénaff (Geomorphology, 2024)

Numerical modelling of tidal sediment dynamics in the Bay of Brest over the Holocene: How the use of a process-based model over paleoenvironmental reconstitutions can help understand long-term tidal deposits? - Matthieu Guillaume Olivier; Estelle Leroux; Didier Granjeon; Pierre Le Hir; Marina Rabineau; Pascal Le Roy; Laure Simplet; Axel Ehrhold; Héloïse Muller (Estuarine, Coastal and Shelf Science, 2023)

Physiological conditions favorable to domoic acid production by three Pseudo-nitzschia species - Aurore Sauvey; Pascal Claquin; Bertrand Le Roy; Orianne Jolly; Juliette Fauchot (Journal of Experimental Marine Biology and Ecology, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Light–dark (12:12) cycle of carbon and nitrogen metabolism in Crocosphaera watsonii WH8501: relation to the cell cycle - Anthony Dron; Sophie Rabouille; Pascal Claquin; Bertrand Le Roy; Amélie Talec; Antoine Sciandra (Environmental Microbiology, 2012)
Summary This study provides with original data sets on the physiology of the unicellular diazotrophic cyanobacterium Crocosphaera watsonii WH8501, maintained in continuous culture in conditions of obligate diazotrophy. Cultures were exposed to a 12:12 light–dark regime, representative of what they experience in nature and where growth is expected to be balanced. Nitrogen and carbon metabolism were monitored at high frequency and their dynamics was compared with the cell cycle. Results reveal a daily cycle in the physiological and biochemical parameters, tightly constrained by the timely decoupled processes of N 2 fixation and carbon acquisition. The cell division rate increased concomitantly to carbon accumulation and peaked 6 h into the light. The carbon content reached a maximum at the end of the light phase. N 2 fixation occurred mostly during the dark period and peaked between 9 and 10 h into the night, while DNA synthesis, reflected by DNA fluorescence, increased until the end of the night. Consequently, cells in G1‐ and S‐phases present a marked decrease in their C : N ratio. Nitrogen acquisition through N 2 fixation exceeded 1.3‐ to 3‐fold the nitrogen requirements for growth, suggesting that important amounts of nitrogen are excreted even under conditions supposed to favour balanced, carbon and nitrogen acquisitions.